Pilates practice companion - Ungaro, Alycea (London New York DK, 2011)
Presents a guide with step-by-step explanations and photographs of Pilates exercises broken down into sections for beginner, intermediate, and advanced fitness levels and listing the physical and mental benefits of each exercise
Includes bibliographical references and index
1
Keywords: Exercise; Physical fitness; Pilates method; Pilates method